Crisis Navigation in Business (Lessons from the Management of Prophet Nuh AS) - Wahyuni, Sri Wahyuni; Asriadi, Ari; Tanjung, Hendri; Bi Rahmani, Nur Ahmadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the crisis in the story of Prophet Nuh AS and apply it to context management crisis in modern business. The bibliographic method is used as the base methodology and involves the selection sources and literature Trusted For understanding implications of management crisis from the perspective various discipline knowledge. Approach bibliography possible analysis comprehensive and systematic to the story of Prophet Nuh AS. Identification crisis in modern business includes crisis financial, reputational, operational, and legal. The impact involves loss of capital, damage image, and sanctions law. Comparison with the story of Prophet Nuh AS shows similarity signs initial, impact potential, and action initial taken. Research result describe that crisis in second context test patience, mental resilience, and need strong leadership. Management lessons from the story of Prophet Nuh AS includes focus on process, quality more from quantity, planning maturity, and management good organization. Study This give outlook about Prophet Nuh AS business planning and strategy, incl vision period long, management risk, communication effectiveness, perseverance, and leadership strong. In conclusion, research This highlighting importance respond crisis with precise, identify opportunity in challenges, and take advantage experience historical for enrich management crisis modern business. Lessons from the story of Prophet Nuh AS can be become guidelines valuable for practitioner business in face dynamics and uncertainty environment business contemporary.